Microscopic Study of Bovine Serum Albumin Adsorption on Zinc Oxide (0001) Surface. Issue 6 (26th January 2021) - Rezek, Bohuslav; Hematian, Hadi; Jíra, Jaroslav; Rutherford, David; Kuliček, Jaroslav; Ukraintsev, Egor; Remeš, Zdeněk
Abstract : Properties and functions of various ZnO materials are intensively investigated in biological systems for diagnostics, therapy, health risks assessment as well as bactericidal and decontamination purposes. Herein, the interface between ZnO and biological environment is studied by characterizing adsorption of bovine serum albumin (BSA) and fetal bovine serum (FBS) using atomic force microscopy with CF4 ‐treated tips. Similar molecular morphologies (thickness around 2 nm) yet different binding forces to ZnO (10–25 nN) are observed. These observations are corroborated by atomic scale simulations of BSA on (0001) ZnO surface using force‐field method and showing rearrangements of Zn surface atoms. Such binding may have an impact also on other properties of ZnO–BSA complex. Abstract : Adhesion of bovine serum albumin (BSA) to zinc oxide (ZnO) surface is studied by atomic force microscopy and atomic scale computing by force‐field method. Pristine BSA adheres more strongly when it is in direct contact with ZnO and not when it is adsorbed as a part of fetal bovine serum.